ANALISIS PERAN KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PADA UNISMA DAN UIN MALIKI MALANG - muhni muhni (Jurnal Ilmu Manajemen (JIMMU), 2020)
This study aimed to analyze 1) the leadership roles characteristics and 2) the influence of the work environment, 3) the performance of employees through work motivation on the Unisma and uin maliki Malang. The hypotheses were 1) the leadership roles influences the performance of employees, 2) the work environment influences on employee performance, 3) the leadership roles influences the work motivation, 4) work environment can influence work motivation, 5) work motivation influences on employee performance and 6 ) the leadership roles and work environment influences the performance of employees through work motivation.This research was a quantitative study with an explanatory approach. Hypothesis was with Path Analysis. The data were obtained by questionnaire given to 113 respondents as permanent employees in Unisma and uin maliki MalangThe results of this study showed that the direct influence: 1) the leadership roles had significant influence on employee performance, namely 35,9%; 2) the work environment had a significant influence on the performance of employees, namely 0,1%, 3) the individual characteristic had significant influence on the work motivation, namely 36,3%; 4) the work environment had a significant influence on the work motivation, namely 63,8%; 5) work motivation had significant influence on the performance of employees, namely 24,7%.. And indirectly influence: 1) the leadership roles had significant influence on the employee performance through work motivation, namely 18,16% 2) work environment had significant influence on the employee performance through work motivation 26,64% Keywords : leadership roles, work environment, employee’s performance, work motivation